Unlocking seagrass germination: divergent roles of strigolactones and smoke-water in Zostera marina (Zosteraceae) - Pieraccini, Riccardo; Picatto, Lisa; Koedam, Nico; Vanreusel, Ann; Dolch, Tobias; Van der Stocken, Tom (Frontiers in Plant Science, 2025)
Seagrasses, such as Zostera marina, play a crucial role in coastal ecosystems, yet the hormonal regulation of their seed dormancy and germination remains poorly understood. Strigolactones (SL) and karrikins (KAR), two plant growth regulators (PGRs) known to regulate germination and development in terrestrial plants, have recently been identified in marine angiosperms. However, their functional roles in seagrasses remain unexplored. Here, we provide the first assessment of SL and smoke-water effects on Z. marina seed germination and seedling development under controlled conditions. Smoke-water is a solution derived from plant combustion that contains a complex mix of bioactive compounds, rich in butenolide compounds such as karrikinolides (e.g. KAR1, KAR2). We tested the effect of ten different concentrations of SL and smoke-water on germination percentage, mean germination time, and seedling growth, considering multiple seed generations. SL significantly promoted germination, particularly at intermediate concentrations (3–15 mg L−1), where germination percentages reached up to 46.7%, as compared to 16.4% in the controls. In contrast, smoke-water treatments reduced germination to below 5% across all tested dilutions, delaying or preventing germination. Moreover, SL enhanced cotyledon growth and accelerated germination, whereas smoke-water consistently inhibited early seedling development. The identification of Z. marina orthologs of key SL and KAR signaling components suggests evolutionary conservation of these pathways in marine plants. Our findings provide new insights into the hormonal regulation of seagrass germination, highlighting both conserved and divergent functions of SL and KAR compared to terrestrial species. These results advance our understanding of hormonal control in marine plant species and hold implications for the conservation and restoration of seagrass meadows.